Culturally aware mentorship: Lasting impacts of a novel intervention on academic administrators and faculty - Womack, Veronica Y.; Wood, Christine V.; House, Stephanie C.; Quinn, Sandra C.; Thomas, Stephen B.; McGee, Richard; Byars-Winston, Angela (PLOS ONE, 2020)
National efforts to address the diversity dilemma in Science, Technology, Engineering, and Math (STEM) often emphasize increasing numbers of historically underrepresented (HU) students and faculty, but fall short in instituting concrete changes for inclusion and belonging. Therefore, increasing the pool of senior faculty who wish to become guides and advocates for emerging scientists from HU populations is an essential step toward creating new pathways for their career advancement. As a step toward achieving this goal, we created a novel eight-hour intervention on Culturally Aware Mentoring (CAM), a program of the National Research Mentoring Network (NRMN) targeted to faculty and administrators. A previous report of surveys at the end of the CAM sessions revealed substantial awareness and knowledge gains, with participants expressing intentions to use and implement new skills they had learned. In this paper, we provide the results of our thematic analysis of qualitative interviews with academic administrators and faculty, 18–24 months after participation in CAM. Interviews were designed to determine: 1) What changes in self-perceptions and interactions occurred as a result of participation in CAM? 2) What specific components of CAM are associated with changes in individual beliefs and practices? 3) How did participants actively make changes after the CAM workshop? 4) What barriers or challenges do participants encounter after the CAM intervention? The results demonstrate the lasting influences of CAM on participants’ awareness of cultural differences, their assumptions about and approaches toward interactions with colleagues and students, and their efforts to change their behaviors to promote inclusive practices in their mentoring and teaching of HU students in STEM. Our findings provide evidence that CAM can be incorporated into existing mentor training programs designed to improve the confidence and capacity of senior research faculty mentors to make culturally-informed, scholar-centered decisions to more deliberately recognize and respond to cultural differences within their mentoring and collegial relationships.